Fate and Effects of Oil Pollutants in Extremely Cold Marine Environments. - Atlas,Ronald M (1976)
Oil biodegradation in Arctic coastal marine waters was modelled using a flow through system incubated 'in situ'. Rates of natural oil degradation were very slow. Addition of nutrients increased degradative losses. Biodegradation did not result in major changes in the relative concentrations of hydrocarbons in crude oil during one summer's incubation. Oil incubated 'in situ' under sea ice showed almost no degradative losses due to chemical or biological weathering during one month's incubation. Low concentrations of soluble/dispersed oil were found to result in sublethal changes in the movement and feeding of Arctic amphipods. Lethality of amphipods exposed to soluble/dispersed oil was concentration dependent. Microbial populations in a lake contaminated by a MOGAS spillage changed in parallel with the movement of the gasoline and appear to be useful as an indication of hydrocarbon contamination. Microorganisms indigenous to the contaminated lake were capable of hydrocarbon degradation and nutrient addition was shown to stimulate degradative losses. (Author)